Principales enemigos naturales de Dione juno (Cramer, 1779) (Lepidoptera: Nymphalidae) en el cultivo de maracuya - Núñez Jaramillo, Gerardo Aniceto (2023)
Passion fruit cultivation Passiflora edulis is highly demanded in the national and international market. Its consumption both in nature or in juice sum for the industry grows annually. Currently, Ecuador registers close to 10 thousand planted hectares, the main producing areas being the coastal region. As passion fruit cultivation increases, it becomes susceptible to attack by countless pest insects, including Dione juno, which is the most important defoliator registered in our country for passion fruit. This document aims to describe the damage and determine the main natural enemies of the passion fruit defoliator worm D. juno. The damage caused by D. juno when consuming the leaves of the passion fruit crop reduces the photosynthetic rate and is considered a pest of economic importance. The egg, larva and pupa stages register attack by natural enemies except the adult stage. Groups of natural enemies such as predators, entomopathogens, and parasitoids attack D. junno, the latter group being the most important natural enemy group recorded for D. juno. Among them, the potter wasps of the Vespide family, is the most important family as a natural enemy of D. juno since it registers more than 52% of predation of all the insects found. Finally, it is recommended that the producers of the passion fruit crop should protect the wasps since these are an ally to the producer and to the integrated pest management against D. juno, the passion fruit defoliator.